PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN DI TOKO ATK HIKMAH - Teguh Imanto; Muhkhamad Edris; Fariz Fariz (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The purpose of this study was to determine the effect of service quality and product quality at the ATK Hikmah Shop on purchasing decisions. Quantitative method is a research methodology used by researchers in this study. The researcher used a research sample of 50 buyers who became customers at the Wisdom Shop. The type of data used in this study is in the form of primary data. The primary data was obtained by the researcher using a questionnaire. Questionnaires were distributed using incidental sampling technique. There are 15 statements each for service quality variables and 18 statements for product quality. As for the purchase decision variable, there are 5 statement items. All statements have been tested statistically and declared valid and reliable. In this study, the data analysis program used is SPSS version 22. From the results of SPSS version 22 data processing, it shows that there is an influence between service quality and product quality on purchasing decisions by consumers at the Wisdom Shop. Keywords: Service Quality, Product Quality, Purchase Decision.